1977
DOI: 10.1007/bf00581370
|View full text |Cite
|
Sign up to set email alerts
|

Dose-dependent stimulation and inhibition of proximal tubular sodium reabsorption by angiotensin II in the rat kidney

Abstract: The effect of val5-angiotensin II on steady-state sodium concentration gradients (deltacNa) was studied in rat proximal tubules by stationary micro-perfusion combined with perfusion of the peritubular capillaries. Angiotensin added to the peritubular perfusion fluid had a biphasic action with stimulation of sodium reabsorption at low doses (10(-12)-10(-10)M) and inhibition at high doses (3 X 10(-7) - 3 X 10(-6)M). Stimulation of transport was also observed with intraluminal angiotensin but only at a dose of 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
171
2
6

Year Published

1982
1982
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 350 publications
(200 citation statements)
references
References 9 publications
21
171
2
6
Order By: Relevance
“…On the other hand, our observed 36% increase of J V with 10 Ϫ11 M ANG II is about twice as great as that observed by the earlier investigators. Our J V data confirm the earlier observations of others, made in a combination of rat (14,23,38) and rabbit (34) PTs, that increasing levels of basolateral ANG II have a biphasic effect on J V . In addition, we observed that increasing levels of basolateral ANG II have a biphasic effect on J HCO 3 .…”
Section: Effects Of Basolateral Ang II On J Hcosupporting
confidence: 92%
“…On the other hand, our observed 36% increase of J V with 10 Ϫ11 M ANG II is about twice as great as that observed by the earlier investigators. Our J V data confirm the earlier observations of others, made in a combination of rat (14,23,38) and rabbit (34) PTs, that increasing levels of basolateral ANG II have a biphasic effect on J V . In addition, we observed that increasing levels of basolateral ANG II have a biphasic effect on J HCO 3 .…”
Section: Effects Of Basolateral Ang II On J Hcosupporting
confidence: 92%
“…We have previously observed that the administration of competitive antagonists to All normalizes the glomerular and tubular responses to glycine during treatment with L-NMMA (12), suggesting that NO normally functions within the proximal nephron to antagonize the anti-reabsorptive effects of All (40). Armed with the new knowledge that glycine increases intrarenal All concentration, we now propose that infusion ofthis substance induces parallel increases in NO and All activity with the glomerular hemodynamic outcome contingent upon the net balance between the two systems.…”
Section: Discussionmentioning
confidence: 99%
“…Investigations of the luminal actions of angiotensin in vivo (Harris & Young, 1977;Wang & Chan, 1990) and in vitro (Li et al, 1994) have indicated that picomolar to nanomolar concentrations of angiotensin II stimulate sodium and bicarbonate transport whereas micromolar concentrations cause inhibition. We have used nonpeptide angiotensin receptor blockers to examine whether endogenously produced angiotensin II in the proximal tubular lumen exerts a modulatory influence upon fluid absorption in the anaesthetized rat.…”
mentioning
confidence: 99%